Bright side eaudiobook Bright side series, book 1. - Holden, Kim (Bright Side, 2015)
Kate Sedgwick's life has been anything but typical. She's endured hardship and tragedy, but throughout it all she remains happy and optimistic (there's a reason her best friend Gus calls her Bright Side). Kate is strong-willed, funny, smart, and musically gifted. She's also never believed in love. So when Kate leaves San Diego to attend college in the small town of Grant, Minnesota, the last thing she expects is to fall in love with Keller Banks. They both feel it. But they each have a reason to fight it. They each have a secret. And when secrets are revealed, some will heal you . . . and some will end you.